1998
DOI: 10.1093/jn/128.8.1342
|View full text |Cite
|
Sign up to set email alerts
|

Threonine and Methionine Are Limiting Amino Acids for Protein Synthesis in Patients with AIDS

Abstract: This study was conducted to identify the most rate-limiting amino acids for whole-body protein synthesis in acquired immunodeficiency syndrome (AIDS) patients. We postulated that an essential amino acid that would be rate limiting in AIDS should have a low basal plasma concentration and should remain at a low level during amino acid infusion. Seven male AIDS patients (median age 37 y, CD4 cell count: 76 mm-3) without any clinically active opportunistic infection during the month before the experiment were infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 31 publications
2
24
1
2
Order By: Relevance
“…Plasma cholesterol (4.52 ± 0.54 mmol·L ) were at normal levels and did not differ from those previously found in AIDS patients without opportunistic infection [12]. By contrast, all patients in the present study had high triglyceride levels (2.67 ± 0.89 mmol·L -1 ).…”
Section: Resultscontrasting
confidence: 61%
See 2 more Smart Citations
“…Plasma cholesterol (4.52 ± 0.54 mmol·L ) were at normal levels and did not differ from those previously found in AIDS patients without opportunistic infection [12]. By contrast, all patients in the present study had high triglyceride levels (2.67 ± 0.89 mmol·L -1 ).…”
Section: Resultscontrasting
confidence: 61%
“…Because shortterm parenteral alimentation enriched with amino acids is capable of reversing the net protein catabolism [10,11], we hypothesize that some specific amino acid deficiencies may limit the utilization of other nutrients. Accordingly, we previously demonstrated that threonine and possibly methionine may be rate-limiting for whole body protein synthesis in HIV-infected patients [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, practical and theoretical arguments have been presented for additional arginine in cardiovascular and pulmonary disorders (7)(8)(9)(10) , for cysteine (11) , leucine (12) and threonine (13) in sepsis, for glutamine in endotoxaemia (10) , and for phenylalanine to support acutephase protein synthesis (14) . In other situations, combinations of AA have been proposed (10,15,16) . Obviously different stages of injury, infection or recovery may require differences in the combinations and absolute quantities of AA.…”
mentioning
confidence: 99%
“…The plasma threonine deficiency observed in 17% of HIV positive patients and the female control population could be due to activation of threonine catabolism and/or synthesis of threonine-rich proteins (Laurichesse et al, 1998). Due to the high threonine concentration in immunoglobulins, threonine deficiency may affect the production of immunoglobulins (Richard and Galanaud, 1995).…”
Section: Discussionmentioning
confidence: 99%